Co‐Catalysis for Hydroamidocarbonylation of Alkynes with Amides over a Bifunctional Ligand‐Based Pd Catalyst - Yang, Da; Zhou, Guang‐Zhao; Zhang, Long‐Li; Liu, Huan (Chemistry, an Asian journal, 2021)
The hydroamidocarbonylation of alkynes with amides allows for the synthesis of α,β‐unsaturated imides with the advantage of 100% atomic economy. Herein, the bifunctional ligand (L1) containing a sulfonic acid group (‐SO3H) and phosphino‐fragment enable the Pd catalyst to accomplish the hydroamidocarbonylation of alkynes with amides. It was found that, due to an intramolecular synergetic effect, the L1‐based Pd‐catalyst exhibited much higher activity than the individual mechanical mixtures of Xantphos‐based Pd‐complex and MeSO3H. The formation and stability of Pd‐H species were promoted by the presence of L1, which was verified by in situ high‐pressure FT‐IR analysis. Under the optimized conditions, the target products of the branched imides were obtained with yields in the range of 46–87% over the L1‐based Pd‐catalyst. Advantageously, as an ionic ligand, the L1‐based Pd‐catalyst could be recycled for 4 runs in the ionic liquid of [Bmim]NTf2 without any obvious activity loss and detectable metal leaching. The hydroamidocarbonylation of alkynes with amides was accomplished over a bifunctional ligand based Pd catalyst.